Hãy rút gọn: $(\sqrt[3]{2}-1)(\sqrt[3]{4}+\sqrt[3]{2}+1)$

Question

Hãy rút gọn: $(\sqrt[3]{2}-1)(\sqrt[3]{4}+\sqrt[3]{2}+1)$

in progress 0
Eden 5 tháng 2021-07-11T09:14:12+00:00 2 Answers 8 views 0

Answers ( )

    0
    2021-07-11T09:15:31+00:00

    ($\sqrt[3]{2}$ – 1)($\sqrt[3]{4}$ + $\sqrt[3]{2}$ + 1)

    = $\sqrt[3]{8}$ + $\sqrt[3]{4}$ + $\sqrt[3]{2}$ – $\sqrt[3]{4}$ – $\sqrt[3]{2}$ -1

    = $\sqrt[3]{8}$ – 1

    = 2 – 1 = 1

    0
    2021-07-11T09:16:10+00:00

    Đáp án:

     

    Giải thích các bước giải:

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )